Diseño, simulación y construcción de un modelo de laboratorio de transporte de pellets (2019)
The article presents how three scaled down industrial machinery models were designed and built as an educational tool to present the transport of particulate material. The literature review showed calculation models for equipment at industrial level, not for laboratory level. There were chosen the most representative means of commercial transport for particulate materials: a conveyor screw, a conveyor belt and a bucket elevator. These three machines were calculated and built in polycarbonate to allow visualization of their internal functioning. The three devices are controlled by a programmable logic controller (PLC) and connected to each other by a SCADA network. The equipment is modular so as not to alter the order of operation, being able to obtain different work sequences. In addition, a man-machine graphic interface (HMI) was developed to supervise and to control the designed equipment. The results of particulate material mass flow obtained are approximately coincident with those estimated, validating the use of calculation models for much lower levels of work. Finally, it is emphasized that the system obtained is an environment for students to implement control techniques using the sensors and motors used in the designs.